2020
DOI: 10.1177/2309499019901172
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis in the lower extremities after femoral neck fracture: A retrospective observational study

Abstract: Purpose: The actual incidence of deep vein thrombosis (DVT) in femoral neck fractures is underestimated. This study aimed to investigate the incidence of DVT in the lower extremities after femoral neck fracture before and after operation. Methods: The clinical data of patients with femoral neck fractures treated at Xi’an Honghui Hospital between July 1, 2016, and December 31, 2018, were collected. The patients were examined with ultrasonography before and after operation and divided into thrombosis and non-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
3
38
0
2
Order By: Relevance
“…Most of the patients with femoral and pelvic fractures are at high risk of venous thromboembolism (VTE) due to hypercoagulable state [ 1 ], trauma and surgical injury, prolonged immobilization, and edema of surrounding tissues, for example, the incidence of preoperative DVT and the postoperative DVT in femoral neck fracture was 32% and 56% respectively [ 2 ]. Previous studies have focused on the analysis and prevention of DVT risk factors after fracture surgery, and seldom focused on the analysis of risk factors before, during and after the entire perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients with femoral and pelvic fractures are at high risk of venous thromboembolism (VTE) due to hypercoagulable state [ 1 ], trauma and surgical injury, prolonged immobilization, and edema of surrounding tissues, for example, the incidence of preoperative DVT and the postoperative DVT in femoral neck fracture was 32% and 56% respectively [ 2 ]. Previous studies have focused on the analysis and prevention of DVT risk factors after fracture surgery, and seldom focused on the analysis of risk factors before, during and after the entire perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al found that the risk of VTE in diabetic patients is 1.44 times higher than that in non-diabetic patients [18] . The ndings of Fu et al [2] and Kang et al [19] also indicated that diabetes increases the risk of DVT. The results of the present study revealed that the prevalence of DVT was signi cantly higher in the diabetic group than in the non-diabetic group (6.2%:5.2%).…”
Section: Discussionmentioning
confidence: 92%
“…Deep vein thrombosis (DVT) is a common complication after trauma, especially after lower extremity fractures [1] . The incidence of preoperative DVT has been reported to be as high as 32% [2] . Underlying fatal effects, such as pulmonary embolism (PE), can be caused by DVT, and research has shown that patients treated for venous thromboembolism (VTE) have approximately twice the length of stay and the total cost of hospitalization as those not treated for VTE [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients with femoral and pelvic fractures are at high risk of Venous thromboembolism(VTE) due to hypercoagulable state [1] , trauma and surgical injury, prolonged immobilization and edema of surrounding tissues,for example, the incidence of preoperative DVT and the postoperative DVT in femoral neck fracture was 32% and 56% respectively [2] .Previous studies focused more on the analysis and prevention of DVT risk factors after fracture surgery, and less on the analysis of risk factors during the whole perioperative period, including pre-operation,introoperation and post-operation.For example, the in uence of preoperative risk factors including chronic obstructive pulmonary disease, pulmonary infection, hypoproteinemia and perioperative blood transfusion on the occurrence and development of DVT. Secondly, anticoagulation therapy, early activities, and lower extremity pneumatic therapy are the main measures for the prevention and treatment of DVT.…”
Section: Introductionmentioning
confidence: 99%